Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Zinc distribution in structural components of high kernel‑zinc maize and its retention after milling - Victor Taleon; Natalia Palacios-Rojas; Yusuf Dollah; Aldo Rosales; Olatundun Kalejaiye; Abebe Menkir (Food Research International, 2025)

Exploring the influence of wood ash, maize cob ash, and tequesquite (alkaline rock) on nixtamalization of maize - Gricelda Vázquez-Carrillo; Leticia García-Cruz; Aide Molina-Macedo; María de la Luz Marrufo-Diaz; Mario E. Rodriguez-Garcia; Rafael Mier-Sainz Trapaga; Charles Bett; Natalia Palacios-Rojas (International Journal of Gastronomy and Food Science, 2024)

Letter to the editor of global food security - Prasanna Boddupalli; Jill E. Cairns; Natalia Palacios-Rojas (Global Food Security, 2024)

From maize to tlayuda, a traditional big-flat leathery tortilla. Effect of two nixtamalization processes on some physicochemical and nutraceutical properties - María Gricelda Vázquez-Carrillo; Roció Toledo-Aguilar; Flavio Aragón-Cuevas; Yolanda Salinas-Moreno; Natalia Palacios-Rojas; David Santiago-Ramos (International Journal of Gastronomy and Food Science, 2023)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

Identification and validation of genomic regions influencing kernel zinc and iron in maize - Vemuri Hindu; Natalia Palacios-Rojas; Raman Babu; Willy B. Suwarno; Zerka Rashid; Rayalcheruvu Usha; Gajanan R Saykhedkar; Sudha K. Nair (Theoretical and Applied Genetics, 2018)

Genome-wide association analysis reveals new targets for carotenoid biofortification in maize - Willy B. Suwarno; Kevin V. Pixley; Natalia Palacios-Rojas; Shawn M. Kaeppler; Raman Babu (Theoretical and Applied Genetics, 2015)

Validation of the effects of molecular marker polymorphisms in LcyE and CrtRB1 on provitamin A concentrations for 26 tropical maize populations - Raman Babu; Natalia Palacios Rojas; Shibin Gao; Jianbing Yan; Kevin Pixley (Theoretical and Applied Genetics, 2013)

Probability of success of breeding strategies for improving pro-vitamin A content in maize - Xuecai Zhang; Wolfgang H. Pfeiffer; Natalia Palacios-Rojas; Raman Babu; Howarth Bouis; Jiankang Wang (Theoretical and Applied Genetics, 2012)